Baicalin Protects Against 17α-Ethinylestradiol-Induced Cholestasis via the Sirtuin 1/Hepatic Nuclear Receptor-1α/Farnesoid X Receptor Pathway - Yang, Jinyu; Xiang, Daochun; Xiang, Dong; He, Wenxi; Liu, Yanan; Lan, Lulu; Li, Guodong; Jiang, Chen; Ren, Xiuhua; Liu, Dong; Zhang, Chengliang (Frontiers in Pharmacology, 2020)
Estrogen-induced cholestasis (EIC) is characterized by impairment of bile formation and secretion. Baicalin is a major flavonoid component of Scutellaria baicalensis, and has been used in the treatment of liver diseases for many years. However, the role of baicalin in EIC remains to be elucidated. In this study, we demonstrated that baicalin showed obvious hepatoprotective effects in EIC rats by reducing serum biomarkers and increasing the bile flow rate, as well as by alleviating liver histology and restoring the abnormal composition of hepatic bile acids (BAs). In addition, baicalin protected against estrogen-induced liver injury by up-regulation of the expression of hepatic efflux transporters and down-regulation of hepatic uptake transporters. Furthermore, baicalin increased the expression of hepatic BA synthase (CYP27A1) and metabolic enzymes (Bal, Baat, Sult2a1) in EIC rats. We showed that baicalin significantly inhibited hepatic inflammatory responses in EIC rats through reducing elevated levels of TNF-α, IL-1β, IL-6 and NF-κB. Finally, we confirmed that baicalin maintains BA homeostasis and alleviates inflammation through Sirt1/HNF-1α/FXR signaling pathway. Thus, baicalin protects against estrogen-induced cholestatic liver injury, and the underlying mechanism involved is related to activation of the Sirt1/HNF-1α/FXR signaling pathway.